Keterampilan Mahasiswa Calon Guru Matematika Dalam Mengembangkan Bahan Ajar - Oktaviani, Dian Nataria; Munadi, M; Ponoharjo, P; Wahyuningsih, Eleonora Dwi; Yuliantiaji, Anggita Putri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
Teaching materials are one of the learning media that teachers must have. Students' skills in compiling teaching materials can be trained and developed through assignments in teaching material development lectures such as preparing LKPD and Teaching Material Modules. The aim of this research is to determine students' skills in developing teaching materials in the form of modules carried out by prospective mathematics teachers. Student skills in compiling teaching material modules in terms of module characteristics for adaptive characteristics are 100%. Students are skilled at self-contained (complete) characteristics of 98.67%. The characteristics of the module in the form of self-instruction (independent learning) have been mastered by students skillfully at 82.22%. The characteristics of user friendly (familiar with the user) are mastered skillfully by students in compiling modules by 100%. The stand alone modules that are prepared are intended to be used without relying on other media or do not have to be used together with other media so that students can master them 100%. Overall, students in paying attention to module components are skilled in a percentage of 69%.